Rudulph Evans papers - Evans, Rudulph, 1878-1960.
Correspondence, reports, financial and legal records, scrapbooks, printed matter, awards and citations, drawings, photographs, and other papers relating to Evans's career as a sculptor. Documents the commission and execution of the statue for the Thomas Jefferson Memorial, Washington, D.C. Subjects include the arts, creative process, literature, Thomas Wiltberger Evans, and Evans family history. Correspondents include Frank P. Evans, Lester L. Evans, and Wilbur Underwood.
Library of Congress Prints and Photographs Division.
Sculptor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Evans, Frank P. -- 1880-1917 -- Correspondence; Evans, Lester L. -- 1886-1923 -- Correspondence; Evans, Thomas Wiltberger, -- 1823-1897.; Jefferson, Thomas, -- 1743-1826 -- Monuments; Jefferson, Thomas, -- 1743-1826 -- Statues; Underwood, Wilbur, -- 1876-1935 -- Correspondence; Art; Creation (Literary, artistic, etc.); Creative thinking; Literature; Monuments -- Washington (D.C.); Sculpture; Sculpture -- Washington (D.C.); Thomas Jefferson Memorial (Washington, D.C.); Artists; Sculptors